Overview of the data security and privacy-preserving of mobile cloud services - Rui-xuan LI; Xin-hua DONG; Xi-wu GU; Wan-wan ZHOU; Cong WANG (Tongxin xuebao)
Compared with the traditional cloud services,the mobi cloud services have the characteristics of the mobile interconnected,flexible end-user applications and convenient data access.However,the rich applications of mobile cloud services bring more security and privacy-leaking problems.The basic concepts,applications and security issues of mobile cloud services were shaded light on,and then describes the architecture of security and privacy-preserving was described,some key technologies were studied in this domain,mainly focusing on the research progress of the security protocols and authentication,access control,integrity verification,mobile trusted computing and the privacy-preserving based on encryption,anonymous and confusion,and the advantages and disadvantages were pointed out respectively.Finally,some future research direction were given at the end.